Relationship Between Prososial Behavior and Intensity of Class Teachers Social Interactions to Special Needs in Inclusive Schools - Hudzaifah Hudzaifah (The Center for Disability Studies and Services Brawijaya University, 2021)
This study aims to find out the relationship of prosocial behavior with the intensity of teacher social interaction towards children with special needs in inclusion schools in Surakarta. The method used in this research is quantitative correlational method. The sampling method is to use purposive sampling method, with a research subject of 30 teachers of inclusion school class in Surakarta. Data collection techniques in this study used questionnaires with the scale of prosocial behavior and social interaction. The result of data analysis using Pearson Correlation Product Moment technique with the help of SPSS 23.0 program obtained correlation of r= 0.919, (p>0.05), thus means Ha rejected and Ho accepted, so it can be concluded that; 1) There is no significant link between prosocial behaviour and the intensity of teacher social interaction towards children with special needs in inclusion schools, 2) The embodiment of prosocial behavior also does not have to give rise to interactions between teachers and students with special needs but a teacher tends to give indirect assistance to students, and 3) The development of increasingly sophisticated technology makes a person, especially children with special needs less social and reduce their social attitudes. So it tends to do things based on its own interests